Responses of Sheep to Haemonchus.Contortus Infection With Respect To Nutritional Enhancement and Innate Resistance - Ben-Gehshir, Mohamed Ali (2000)
Gastrointestinal parasitism, in particular caused by Haemonchus contortus, is the major source of parasitic gastro-enteritis in tropical countries and is associated with large economic losses. This study was conducted to investigate the enhancement of responsiveness of sheep to H contortus infection by dietary protein supplementation and by selecting and breeding for resistance to H contortus. In the first experiment, thirty two, 3 month old Dorsimal lambs were used to study the influence of dietary protein supplementation on H contortus infection. Lambs were offered a complete basal ruminant diet (15% crude protein; CP), with or without fish meal as a source of rumen bypass protein (19% CP). Lambs from each dietary treatment group were given either a 7-week trickle infection with H. contortus infective larvae or remained uninfected. All lambs were drenched with anthelmintics at week 8 post-infection, then challenged with a single dose of 5000 H. contortus L3 one week later and killed 14 days post-challenge. Supplementation lower faecal egg counts (FECs) in trickle infected lambs. The non-supplemented, trickle infected lambs had lower packed cell volume (PCY), haemoglobin (Hb) and plasma protein (PP). Although no obvious eosinophilia was observed and peripheral eosinophil and abomasal worm counts were not significantly different among the four groups, supplementation, had significant effect on eosinophil and mast cells in the abomasal mucosa (P<0.05). Significant correlation was recorded between worm burdens and tissue cell counts. In the second experiment, Santa Ines sheep were selected and bred for resistance to H. contortus infection. A foundation population of 123 lambs of 3-4 months of age from two flocks was used. Animals with low FEC (mean <2725) following naturally acquired infection were deemed as high responder (HR) animals that were resistant to strongly infection, while animals with high FEC (mean >3675) were classified as low responder (LR) animals that were more susceptible. The HR and LR selected lambs were transferred to UPM and treated to remove the field infection. The lambs were kept indoor and subsequently artificially infected with a single oral dose of 10000 H. contortus L3. At the age of 12 months, HR males were mated to HR females and LR males to LR females. The offspring of these matings were in tum artificially challenged with 10000 H. contortus L3 upon weaning to confirm their responder status . The post-challenge FEC, PCV, PP and body weights of these lambs were monitored. The FEC of HR animals were significantly (P<O.OOl) lower than that of LR animals in field and post-challenge. The PCV and PP of LR animals were significantly lower than that of the HR animals. There was a significant, positive correlation between FECs from field and experimental infections and FECs of the offspring and their sires and dams. This study suggests it is possible to segregate sheep into HR and LR using simple parasitological criteria supported by PCV and PP and that resistance to H contortus is inherited.